Avaliação histomorfométrica da regeneração óssea com a utilização de plasma rico em fibrina (PRF) associado ou não a osso bovino em defeitos ósseos na calvária de ratos - Oliveira, Marina Reis (2014)
Currently, there is much discussion about the use of platelet concentrate to promote tissue regeneration, especially bone regeneration. Platelet-rich plasma (PRP) is still widely used for this purpose although there are doubts on its real therapeutic ability. Fibrin-rich plasma (PRF), described as a second generation of platelet concentrates, appears to promote more promising effects on tissues under repair. This study aimed to perform a histomorphometric evaluation of bone regeneration using PRF associated or not with bovine bone (Bio-Oss) in the calvaria of rats. It was used 56 rats, being 8 donors rats and others were divided into 6 groups of 8 animals each according to the treatment received: CA (autogenous clot), CH (homogenous clot), PRF-a (autogenous PRF), PRF-h (homogenous PRF), BO (Bio-Oss) and BOPRF (Bio-Oss associated with PRF). And 4 rats in each group were euthanized after 30 and 60 days postoperatively. New bone area (BA) was calculated as a percentage of the total area (TA) of the original defect. Values obtained were subjected to analysis of variance (ANOVA) and Tukey's test (p <0.05). The highest mean percentage of new bone was observed in BOPRF group (58.8200% ± 4.8042) which was significantly greater than the following groups: CH (26.8800% ± 4.8042), CA (18.6262% ± 4.8042), PRF-a (22.4062 ± 4.8042) and PRF-h (37.9387% ± 4.8042). No statistical difference was observed in the assessment among groups, between BOPRF (58.8200% ± 4.8042) and BO (41.7175% ± 4.8042); and among periods (60 days), between BOPRF (63.5875% ± 4.8042) and BO (57.3450% ± 4.8042). The results obtained indicate that PRF had a positive effect on bone regeneration particularly when associated with Bio-Oss.